Abnormal behaviour of sporadic E-layer during the total solar eclipse of 22 July 2009 near the crest of EIA over India. Issue 10 (15th November 2019) - Tiwari, Prabhakar; Parihar, Navin; Dube, Adarsh; Singh, Rajesh; Sripathi, S.
Abstract: In this study we present the behaviour of sporadic E-layer during a total solar eclipse (TSE) which occurred during the dawn/sunrise hours over a site located in the path of totality. A Canadian Advanced Digital Ionosonde (CADI) was operated at Allahabad (25.4° N, 81.9° E), a low latitude station located near the crest of equatorial ionization anomaly (EIA) in the Indian subcontinent to study the ionospheric effects of 22 July 2009 TSE. Corresponding to the eclipse period, a gradual increase of ftEs (top frequency of Es layer) in the 4–5 MHz range was seen on the control days. On 22 July (the TSE day), correlated changes in ftEs coinciding with the TSE progression was noted – (i) sharp decrease near first and second contact of TSE, (ii) an increase after first and second contact, and (iii) wavelike fluctuations in ftEs variation during eclipse hours and beyond. Much higher ftEs values were noted during the TSE hours in comparison to that seen on usual days. Strong blanketing Es layer developed during the TSE hours and persisted for slightly longer duration than its usual occurrence time. Near the TSE totality, slight lowering of the base height of Es layer was also noted.